The dynamic changes in the number of uterine natural killer cells are specific to the eutopic but not to the ectopic endometrium in women and in a baboon model of endometriosis - Josephine A. Drury; Kirstin L. Parkin; Lucy Coyne; Emma Giuliani; Asgerally T. Fazleabas; Dharani K. Hapangama (BMC, 2018)
Abstract Background Endometriosis is a common condition associated with growth of endometrial-like tissue beyond the uterine cavity. Previous reports have suggested a role for uNK cells in the pathogenesis of endometriosis postulating that survival and accumulation of menstrual endometrial tissue in the peritoneal cavity may relate to a reduction in the cytotoxic activity of peripheral blood NK cells. We aimed to assess the differences in percentage of uNK cells and their phenotypical characterization in eutopic and ectopic endometrial samples from women with and without endometriosis and baboons with induced endometriosis. Methods Eutopic and ectopic endometrial samples from 82 women across the menstrual cycle with/without endometriosis and from 8 baboons before and after induction of endometriosis were examined for CD56 and NKp30 expression with immunohistochemistry, quantified using computer assisted image analysis. Curated secretory phase endometrial microarray datasets were interrogated for NK cell receptors and their ligands. In silico data was validated by examining the secretory phase eutopic endometrium of women with and without endometriosis (n = 8/group) for the immuno-expression of BAG6 protein. Results The percentage of uNK cells increased progressively from the proliferative phase with the highest levels in the late secretory phase in the eutopic endometrium of women with and without endometriosis. The percentage of uNK cells in ectopic lesions remained significantly low throughout the cycle. In baboons, induction of endometriosis increased the percentage of uNK in the ectopic lesions but not NKp30. Published eutopic endometrial microarray datasets demonstrated significant upregulation of NKp30 and its ligand BAG6 in women with endometriosis compared with controls. Immunohistochemical staining scores for BAG6 was also significantly higher in secretory phase eutopic endometrium from women with endometriosis compared with the endometrium of healthy women (n = 8/group). Conclusions The dynamic increase in the percentage of uNK cells in the secretory phase is preserved in the endometrium of women with endometriosis. The low number of uNK cells in human and baboon ectopic lesions may be due to their exaggerated reduction in hormonal responsiveness (progesterone resistance).